The Effectiveness of Mindfulness-Based Cognitive Therapy on Psychological Distress and Sleep Quality in Women with Irritable Bowel Syndrome - Shapouri, Tahereh; Jafari, Alireza (Psychology of Woman Journal, 2026)
Objective: The present study aimed to determine the effectiveness of mindfulness-based cognitive therapy on psychological distress and sleep quality in individuals with irritable bowel syndrome. Methods and Materials: This study employed a quasi-experimental and applied research design using a pretest–posttest control group format. The statistical population consisted of all women diagnosed with irritable bowel syndrome who attended hospitals and medical centers in Tonekabon in 2024. The research sample comprised 30 participants selected through purposive sampling and randomly assigned to experimental (n = 15) and control (n = 15) groups. The research instruments included the Kessler Psychological Distress Scale (Kessler, 2002) and the Pittsburgh Sleep Quality Index (Buysse et al., 1989). Data were analyzed using multivariate analysis of covariance (MANCOVA) and univariate analysis of covariance (ANCOVA). All statistical analyses were conducted using SPSS version 27. Findings: The results indicated a significant difference between the intervention and control groups in the mean scores of psychological distress and sleep quality (P < .001). Conclusion: The findings favored the experimental group. Overall, the results demonstrated that mindfulness-based cognitive therapy effectively reduced psychological distress and improved sleep quality among women with irritable bowel syndrome.